1999
DOI: 10.1136/fn.80.1.f34
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin concentrations and transitional circulation in preterm infants requiring mechanical ventilation

Abstract: Results-The mean 6KPGF 1 concentrations were higher than adult concentrations at 5 (515 pg/ml) and 24 (255 pg/ml) hours. There was no association with gestational age. Raised 6KPGF 1 concentrations were related to increased need for mechanical ventilation and severity of respiratory disease. At 5 hours, increased 6KPGF 1 concentrations were associated with larger PDA and at 24 hours with larger PDA and higher left ventricular output. Infants with higher 6KPGF 1 concentrations were more likely to develop clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…To circumvent this problem, we achieved augmentation of PGI 2 production by adenovirus-mediated gene transfer of COX-1 and PGIS. Our results demonstrate that Ad-COP1 infection augmented PGI 2 level to ϳ300 pg/ml, which is within the range of results of clinical studies showing that under various stresses, the PGI 2 level can vary from Ͻ50 to Ͼ500 pg/ml (39,40).…”
Section: Discussionsupporting
confidence: 69%
“…To circumvent this problem, we achieved augmentation of PGI 2 production by adenovirus-mediated gene transfer of COX-1 and PGIS. Our results demonstrate that Ad-COP1 infection augmented PGI 2 level to ϳ300 pg/ml, which is within the range of results of clinical studies showing that under various stresses, the PGI 2 level can vary from Ͻ50 to Ͼ500 pg/ml (39,40).…”
Section: Discussionsupporting
confidence: 69%
“…This gene is responsible for the production of prostaglandin I2 (prostacyclin), a potent vasodilator which plays a critical role in fetal patency of the ductus arteriosus (reviewed in (25)). It is possible that alterations in the regulation of this gene could lead to abnormal postnatal closure of the DA in a preterm infant, since prostacyclin levels are elevated in preterm infants and the concentration of a prostacyclin metabolite (6-ketoprostaglandin F1-alpha) has been shown to correlate with ductal diameter (26). …”
Section: Discussionmentioning
confidence: 99%
“…Because of their importance in the maintenance and control of cerebral hemodynamics, it has previously been suggested that indomethacin may exert its cerebral hemodynamic effects through inhibition of prostanoid production (14,19). Postnatal cerebral hemodynamic adaptation is mediated by changes in prostanoid production (1,11,12,17). It is therefore possible that the cerebral hemodynamic response to indomethacin in the unstable immediate postnatal period will be dependent on the degree to which cerebral hemodynamics have adapted to postnatal life.…”
mentioning
confidence: 99%